Stronger impact of urea application than incorporation of Chinese milk vetch (Astragalus sinicus L.) on nirK-denitrifying bacterial communities in a Chinese double-rice paddy - Jiangwen Nie; Yadong Yang; Bin Wang; Zhangyong Liu; Bo Zhu (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2021)
The impact of Chinese milk vetch (Astragalus sinicus L., CMV) incorporation on the nirK-denitrifying bacteria remains unknown. Here, the diversity and the composition of nirK-denitrifying bacterial communities in a double-rice paddy soil were estimated by using Illumina MiSeq sequencing under four fertilisation treatments: no fertilisation (CK), vetch incorporation (CMV), urea (N200) and combined application of vetch and urea (CMV+N100). Compared with CK, N200 increased Shannon index by 10.5% in early rice season, whereas CMV did not change the Shannon index and Chao1 index in both seasons. Proteobacteria and Bradyrhizobium were the most abundant phylum and genus for nirK-denitrifying bacterial communities, respectively. Most variations in abundance of genus components of nirK-denitrifying bacterial communities as affected by the application of urea were detected in late rice season. Principal coordinates analysis showed that effect of CMV on the nirK-denitrifying bacterial communities was weaker than application of inorganic fertiliser (N200 and CMV+N100). Furthermore, redundancy analysis showed that soil was the key factor driving nirK-denitrifying bacterial communities. Our results indicated that the response of the nirK-denitrifying bacterial communities is more sensitive to urea than vetch, suggesting the combination of vetch and urea can be considered as an alternative N resource to inorganic fertiliser.